2022
DOI: 10.1177/00469580221081433
|View full text |Cite
|
Sign up to set email alerts
|

Does the Application of International Classification of Disease Codes for the Cause of Death on Death Certificates Reduce Garbage Codes?

Abstract: Introduction This study aimed to determine if applying International Classification of Diseases (ICD) disease codes directly as the cause of death (COD) on death certificates (DCs) instead of writing or typing the COD could reduce the use of garbage codes. Methods Beginning in April of 2016, a documentation process change was made, retiring the process of hand-writing or typing the COD onto DCs to directly applying ICD disease codes that were registered during the patient’s course of treatment. The DCs issued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…DC errors were divided into major and minor errors based on previous literature. 1 2 3 4 5 6 8 9 10 11 12 13 14 15 16 17 18 22 23 Major errors were defined as errors that could affect COD determination, and other errors were defined as minor errors. The detailed classification and examples of errors are shown in Tables 1 and 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DC errors were divided into major and minor errors based on previous literature. 1 2 3 4 5 6 8 9 10 11 12 13 14 15 16 17 18 22 23 Major errors were defined as errors that could affect COD determination, and other errors were defined as minor errors. The detailed classification and examples of errors are shown in Tables 1 and 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In the second evaluation, which included the participation of an additional EP with previous experience in conducting studies related to DC errors, the final errors were judged after discussion among the five EPs. 6 10 16 17 22 All evaluators who participated in the judgment of errors received guidelines for DC writing training and made judgments with sufficient knowledge. 24 25 26 27 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Errors were divided into major and minor according to the previously described criteria 2,3,5, [10][11][12][14][15][16][17][18] . The errors are listed in Table 1 and Appendices 1, 2 (https://doi.org/10.22470/pemj.2022.00444).…”
Section: Definitions Of the Errors And Variables Of Interestmentioning
confidence: 99%
“…Previous studies [15][16][17]20,29,39,40 have reported that certifiers' education has a substantial impact on the quality of DC completion. Therefore, improving the certifiers' knowledge and skills for completing DCs according to the WHO guidelines, using a robust quality control mechanism for DC documentation, and planning automated systems for recording, selecting, and coding the death causes can play a key role in enhancing the completion quality of DCs, their coding, and finally, the extracted mortality statistics.…”
Section: Correlation Between Minor Errors With Other Variablesmentioning
confidence: 99%